Pleuroparenchymal Fibroelastosis as a Late-Onset Pulmonary Toxicity after Treatment with Anticancer Chemotherapy for High-Risk Neuroblastoma - Satoshi Yokoyama; Risa Kanai; Daisuke Fukao; Keigo Hamahata (Case Reports in Pediatrics)
Pleuroparenchymal fibroelastosis (PPFE) is a rare, progressive, restrictive lung disease characterized by hypercarbic respiratory failure. In pediatrics, it has been described in patients with a history of malignancy who have received a bone marrow transplant, chemotherapy, or radiotherapy. It is characterized by pleural thickening, fibrosis, subpleural elastosis, and intraalveolar collagen deposits. Survival is poor, and the only therapy is lung transplantation. Here, we report a patient who developed PPFE as a late-onset pulmonary toxicity after treatment with anticancer chemotherapy for high-risk neuroblastoma (NB).